Transformation of urban land use in the era of global change: tools for regulating spatial development - Titenko, I.; Hunko, L. (Land Management, Cadastre and Land Monitoring, 2024)
Abstract. Recent transformations in the world, such as urbanisation, industrialisation and globalisation, have significantly changed ecosystems, human settlements, economies and politics. These changes have important implications for the environment, public health and socio-economic development. Foreign authors point out the uniqueness of a comprehensive study of urban land use, which covers various scientific disciplines and analyses anthropogenic adaptations of territories to meet social needs. Taking into account social, economic and environmental aspects in urban land use planning is important for sustainable development, which can improve the quality of life of the population and preserve environmental well-being. This article examines the impact of market forces on urban expansion from an economic perspective. As long as the benefits of using urban land outweigh those of agricultural land, cities continue to grow. However, the market mechanism can lead to an unequal distribution of benefits and loss of public land resources. Governments use policy instruments to control urban expansion, including defining urban growth boundaries, transferring land development rights, buying out state land, issuing building permits, setting infrastructure constraints, charging for environmental impacts, and more.Key words: urban land use, policy instruments, uncontrolled urban sprawl, preservation of agricultural land, land use planning, market mechanism, globalisation, public authorities, zoning.
Keywords: urban land use; policy instruments; uncontrolled urban sprawl; preservation of agricultural land; land use planning; market mechanism; globalisation; public authorities; zoning